Мовленнєвий код сайтів новин: презентативність та персоналізація - Акімова, Наталія (Lesya Ukrainka Eastern European National University, 2017)
The article is focused on how news site speech code elements are embodied by means of presentation and personalization. Among the main research methods are analysis and synthesis, descriptive text analysis, linguocultural and concept text analysis, modeling, method of semantic and pragmatic interpretations, contextual observation and comparative analysis are used. Definition of presentation and personalization are presented, examples from the most popular news sites of UKRNET (Korrespondent.net, LB.ua) and Runet (RosBusinessConsulting, RIA Novosti) are analyzed. Such problems are accented as how these features complicate news text understanding, what psychological and neurolinguistic difficulties they cause, what psycholinguistic mechanisms are involved in understanding process of these news announcements. Traditional communicative code is broken and the readers’ consciousness is manipulated. The user unknowingly pays attention to these texts, he spontaneously remembers them and then uses as a cliché or a model in his/her speech. Verbal behavior changes, in their turn, lead to changes in thinking and understanding of reality. The research is carried out in the context of the theory of deviant speech units, achievements of modern linguistics, cognitive science, psychology and neuroscience. У статті розглянуто елементи мовленнєвого коду сайтів новин, реалізовані засобами презентативності та персоналізації. Для цього використані методи аналізу та синтезу; описового, лінгвокультурного та концептуальнного аналізу тексту, моделювання, метод семантичних і прагматичних інтерпретацій, контекстне спостереження та порівняльний аналіз. Надано дефініції презентативності та персоналізації, наведено приклади з найбільш популярних новинних сайтів укрнету (Корреспондент.net, LB.ua) та рунету (РосБизнесКонсалтинг, РИА Новости). Висвітлено питання, яким чином ці риси ускладнюють розуміння текстів новин, які вони зумовлюють психологічні та нейролінгвістичні труднощі, які психолінгвістичні механізми залучено в процесі розуміння таких новинних анонсів. Зазначено, що при цьому порушується традиційний комунікативний кодекс та відбувається маніпулювання свідомістю читачів. Користувач несвідомо звертає увагу на такі тексти, мимовільно їх запам’ятовує і потім використовує як кліше або моделі у власному мовленні. У свою чергу, зміна мовленнєвої поведінки призводить до зміни способу мислення і розуміння реальності. Дослідження здійснюється в контексті теорії девіантних мовленнєвих одиниць, досягнень сучасної лінгвістики, когнітивістики, психології та нейронауки.
Keywords: інтернет-новина; інтернет-комунікація; мова інтернету; розуміння; психолінгвістика; нейролінгвістика; інтернет-лінгвістика; online news; online communication; Internet language; understanding; psycholinguistics; neurolinguistics; Internet linguistics